Methodological Dominants to the Financial Support for Regional Development in the Context of Postwar Recovery - Bondaruk, T. H.; Onyshko, S. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The authors elaborate on the basic methodological dominants to the financial support of regional development, which can be used in the process of postwar recovery of the regions. They include scenario planning, SWOT and PESTLE analysis, mission-oriented method, using geo-information systems and digital technologies in planning of socio-economic development. Approaches to the integration of digital decisions in the processes of financial support to regional development are proposed, enabling to enhance the quality of monitoring, control and adjustments of regional strategies in compliance with change in the external environment. Particular emphasis is placed on the issues of adapting international experiences of financial support to the recovery of territories formerly hit by crisis. Successful practices of European countries show that using the principles of decentralization, public-private partnership and integration of local communities into the process of strategic planning of financial support is a premise for the effective regional development. The cooperation with international financial organizations like World Bank, EBRD or IMF will promote long-term investment inflow, being critically important for the financial support of regional development and recovery of the Ukrainian economy. The key areas of financial support for regional development, covering economic, social and environmental dimensions, are outlined. Special emphasis is placed on creating the schemes for encouragement of local business, supporting innovation-based entrepreneurship, fostering the labor supply and implementing environmentally sustainable decisions. An important component in the strategic planning of the financial support to regional development is building up an effective public administration system and creating the conditions for private capital investment in rehabilitation of regional infrastructures. The authors proposed a structural model for the strategic planning of financial support to regional development, incorporating analytical, organizational, resource, and implementation & monitoring modules. The analytical module is designed to determine the strategic potential of a region and assess its socio-economic performance. The organizational module has the schemes for coordination between state authorities, business and public sector, enabling for a holistic management of regional development. The resource module is designed for searching financial, material and human resources required for the implementation of objectives. The results of the study confirm the need to use a multitiered approach to the financial support of regional development in the postwar recovery context, combining adaptation to the current conditions and long-term sustainable development goals.